Synonymical notes on Neotropical Cerambycidae (Insecta, Coleoptera) - Monné, Miguel A.; R., Juan Pablo Botero (Zootaxa, 2011)
New synonymies are proposed: in Macrotomini, Prioninae, Strongylaspis (Curitiba) scheerpeltzi Tippmann, 1953 = Strongylaspis (Curitiba) brunni Lameere, 1903; in Cerambycini, Cerambycinae, Amphelictus jumerim Martins & Monné, 2005 = Amphelictus fortunensis Eya & Chemsak, 2003, Amphelictus novellus Martins & Monné, 2005 = Amphelictus fuscipennis Eya & Chemsak, 2003, Amphelictus aibussu Martins & Monné, 2005 = Amphelictus abaiba Martins & Monné, 2005, and in Forsteriini, Lamiinae, Paraphaula Fuchs, 1963 = Udamina Thomson, 1868 and Paraphaula porosa Fuchs, 1963 = Udamina leprieurii Thomson, 1868.